2013
DOI: 10.4055/cios.2013.5.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Urinary Retention Following Anterior Cervical Spine Surgery for Degenerative Cervical Disc Diseases

Abstract: BackgroundPostoperative urinary retention (POUR) may cause bladder dysfunction, urinary tract infection, and catheter-related complications. It is important to be aware and to be able to identify patients at risk of developing POUR. However, there has been no study that has investigated the incidence and risk factors for the development of POUR following anterior cervical spine surgery for degenerative cervical disc disease.MethodsWe included 325 patients (164 male and 161 female), who underwent anterior cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 16 publications
1
32
2
Order By: Relevance
“…However, few studies have assessed POUR with lumbar spine surgery. (5,11) Our study documented a rate of 16.5% occurrence of POUR in patients who underwent spinal surgery which is considerably higher than previous reports on POUR in spine surgery, such as that by Atschulet al (5) (8.8%), Gandhi et al (4) (5.6%), and Jung et al (11) (11.1%).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…However, few studies have assessed POUR with lumbar spine surgery. (5,11) Our study documented a rate of 16.5% occurrence of POUR in patients who underwent spinal surgery which is considerably higher than previous reports on POUR in spine surgery, such as that by Atschulet al (5) (8.8%), Gandhi et al (4) (5.6%), and Jung et al (11) (11.1%).…”
Section: Discussioncontrasting
confidence: 52%
“…(1,2,3,6,5) These variations can be attributed to the several factors, including the variable definitions used to define POUR, type of surgery performed, type of anaesthesia, and use of opioid analgesia that affects bladder function. (1,9,10,7,11) Another contributing factor to the variable incidence rates is the fact that variable definitions have been used in these studies to establish POUR. The present study used a clinical definition for defining POUR, and this may be a limitation, particularly in the case of obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major risk factors included male sex, advanced age, BPH, myelopathy, and the use of meperidine. 9 Both studies suggested that the incidence of POUR may be associated with longer length of hospitalization. However, these previous studies were limited in their methodology by focusing primarily on postoperative pain medications as opposed to a variety of intraoperative medications.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6] However, the data is limited in the context of spinal procedures. [7][8][9] Several studies have investigated POUR following spinal procedures. However, these studies have focused on non-modifiable demographic risk factors such as gender and age.…”
Section: Introductionmentioning
confidence: 99%